THE POPULATION OF NITROGEN FIXING BACTERIA AND PHOSPHATE SOLUBILIZING BACTERIA IN THE RHIZOSPHERE FROM GUNUNG HALIMUN NATIONAL PARK - Widawati, Sri; Suliasih, Suliasih (Research Center for Biology-Indonesian Institute of Sciences, 2001)
The biodiversity of nitrogen fixing bacteria (Rhizobium, Azotobacter and Azospirillum) and phosphate solubilizing bacteria in rhizosphere collected from Gunung Halimun National Park were studied.Bacterial population was counted from soil rhizosphere collected from various ecosystem types (determined based on elevation) namely 600 m, 1000 m, 1100 m, 1500 m and 1800 m above sea level.The results showed that the highest population of N-fixing and P solubilizing bacteria at Cikaniki (1100 asl) are founded in the plant rhizosphere of Schima wallichii in plot Suzuki A I and Altingia exelsa in Suzuki A III,at Gunung Botol area is in 1000 m asl,and Ciptarasa area is in 600 m asl.The population of N-fixing and P solubilizing bacteria at Gunung Halimun was influenced by the vegetation type, soil pH,and the elevation of area. Rhizobium, Azotobacter, Azospirillum (N-fixing bacteria); Pseudomonas sp, and Bacillus megaterium (P solubilizing bacteria), are most dominant at 600 m, 1000 m and 1100 m asl.